Изучение минерального состава и структуры уролитов жителей томского района (г. Томск); Урология; № 2 - Севостьянова О. А. Ольга Александровна; Бощенко В. С. Вячеслав Семёнович; Осадчий В. К. Владислав Константинович; Парначев В. П. Валерий Петрович; Полиенко А. К. Александр Константинович (2017, 2017)
Заглавие с экрана